Crowd Control. - Hoffmann, Leah (Communications of the ACM, 2009)
The article discusses crowdsourcing computer applications. Crowdsourcing is a distributed problem-solving process in which answers are sought online for specific questions that computers can't solve, the article states. Other names for the process include human computation and computer-aided micro-consulting. Also discussed is James Surowiecki's book, "The Wisdom of Crowds," the amateur and often anonymous workers that execute the tasks in return for various incentives, and Mechanical Turk, a crowdsourcing program from Amazon.